Clinicopathologic characteristics and oncologic outcomes in adenosarcoma of gynecologic sites - Jessie Y. Li; Levent Mutlu; Joan Tymon-Rosario; Wafa Khadraoui; Nupur Nagarkatti; Pei Hui; Natalia Buza; Lingeng Lu; Peter Schwartz; Gulden Menderes (Elsevier, 2022)
Objective: To examine clinicopathologic characteristics and oncologic outcomes of patients diagnosed with Mullerian adenosarcoma and to evaluate ovarian preservation as a practical management option in early-stage disease. Methods: A retrospective review was performed of 31 patients treated for uterine, ovarian, or cervical adenosarcoma at our institution between 1/2000-3/2020. Recurrence-free survival (RFS) and overall survival (OS) were analyzed with Kaplan-Meier estimates, the log-rank test, and Cox proportional hazards regression. Results: Median age was 51 years (IQR: 41-68). Primary sites included uterine corpus (n = 23, 74.2%), uterine cervix (n = 7, 22.6%), and ovary (n = 1, 3.2%). Surgical management primarily consisted of total hysterectomy +/- bilateral adnexectomy +/- lymph node dissection. Fifteen (48.1%) patients underwent lymph node dissection; no patients had positive nodes. Ovaries were preserved in 6 (19.4%). Twenty-two (71.0%) patients received no adjuvant therapy, 4 (12.9%) received chemotherapy, 1 (3.2%) received chemoradiation, and 3 (9.7%) received hormonal therapy. Sarcomatous overgrowth (p = 0.04), high grade histology (p = 0.002), and greater depth of myometrial invasion (p = 0.001) were associated with decreased RFS. None of the 6 patients with ovarian preservation had recurrences. At last follow up, 21 patients (67.7%) had no evidence of disease, 7 (22.6%) were deceased due to disease, and 3 (9.7%) were deceased due to non-cancerous reasons. Conclusions: Uterine adenosarcoma appears to have a relatively good prognosis, especially in the absence of risk factors, such as sarcomatous overgrowth, high grade histology, and deep myometrial invasion. Ovarian preservation may be a feasible management option with non-inferior outcomes for premenopausal women with early-stage disease. Future studies including larger patient cohorts are needed for this rare disease.